Access to optically active tetrafluoroethylenated amines based on [1,3]-proton shift reaction - Kabumoto, Yuta; Yoshimoto, Eiichiro; Xiaohuan, Bing; Morita, Masato; Yasui, Motohiro; Yamada, Shigeyuki; Konno, Tsutomu (Beilstein Journal of Organic Chemistry, 2024)
Treatment of various (R)-N-(2,2,3,3-tetrafluoropent-4-en-1-ylidene)-1-phenylethylamine derivatives with 2.4 equiv of DBU in toluene at room temperature to 50 °C for 24 h led to a smooth [1,3]-proton shift reaction with a high chirality transfer, affording the corresponding rearranged products in acceptable yields. Without purification, these products were subjected to acid hydrolysis and the subsequent N-Cbz protection, providing the optically active tetrafluoroethylenated amides in moderate three-step yields.
Keywords: amine; chirality transfer; [1,3]-proton shift reaction; tetrafluoroethylene fragment